Evolution of the magnetic structure in overdoped antiferromagnetic La1-xCaxMnO3 (0.51? x ? 0.69) manganites: A neutron diffraction study - Pissas, M.; Stamopoulos, D.; Arulraj, A.; Prassides, K. (PHYSICAL REVIEW B, 2023)
The La1-xCaxMnO3 series of compounds with antiferromagnetic ground states (x 1/2) have been extensively studied due to the novel spin, orbital, and charge-ordering states observed when the calcium concentration is a simple fraction (x = 1/2, 2/3, and 3/4). The ground states of these compositions have been explained by the Goodenough charge, orbital, and spin ordering model. An important issue remaining is the elucidation of how the ground state changes when x is not a simple number. Here we study the magnetic structure of La1-xCaxMnO3 for 0.51 x 0.69 using powder neutron diffraction measurements supported by magnetization data. For compositions with 0.51 x 0.56, the magnetic structure, which we term as an incommensurate charge exchange (CE) structure can be described by two propagation vectors kC = [1/2, 0, 1/2] and kE = [6E, 0, 1/2]. In the second one, the component parallel to the a* axis of the reciprocal lattice changes with the Mn4+ concentration x as 6E approximate to x - 1/2 providing, thus, an unambiguous signature of the adoption of an incommensurate magnetic structure. As x gradually increases, the diffraction data reveal that two magnetic phases-one adopting the incommensurate CE, and one adopting the commensurate "2/3" magnetic structure-co-exist in the concentration regime of 0.57 x 0.61. Around the simple fraction x = 2/3, the magnetic structure can be also described by three propagation vectors, the commensurate kE = [0, 0, 1/2], kC = [1/2, 0, 1/2], and an incommensurate k2/3 = [1/3 + 62/3, 0, 1/2] propagation vector with 62/3 taking negative/zero/positive values for x smaller than/equal to/larger than 2/3, respectively. Our experimental results for 0.51 x 0.56 are neither in favor of a stripe structure consisting of a fine mixture of x = 1/2 and x = 2/3 phases (phase separation) nor of a defect structure in which an appropriate amount of Mn3+-O sheets have been replaced by Mn4+-O sheets (defect structure). A sinusoidal modulated structure has been used as a possible candidate in explaining the experimental neutron diffraction magnetic Bragg peaks. This result may be linked to the presence of a mixed orbital state of the manganese ions.